MELOXICAM: USE PROSPECTS IN ERYTHEMA NODOSUM - O N Egorova; B S Belov; R M Balabanova; Yu A Karpova; O N Egorova; B S Belov; R M Balabanova; Yu A Karpova (Современная ревматология)
Nonsteroidal anti-inflammatory drugs are widely used in rheumatology in the complex therapy of pain syndrome. The paper describes the pathophysiological mechanisms of development of acute and chronic pain. The action of cyclooxygenases (COX) (types 1 and 2) is detailed. The key role of COX-2 in the induction and transmission is shown. The stepwise course of meloxicam relieves pain syndrome in the shortest possible time. The presented case demonstrates the analgesic and anti-inflammatory effects of meloxicam (Movalis) in a female patient with erythema nodosum.